Μ‐stability of impulsive differential systems with unbounded time‐varying delays and nonlinear perturbations. (19th October 2012) - Wang, Lei; Li, Xiaodi
<x xml:space="preserve">Abstract</x> This paper is concerned with the problem of μ‐stability of impulsive differential systems with unbounded time‐varying delays and nonlinear perturbations. Some μ‐stability criteria, which depend on the range of distributed delay and the decay rate of discrete delay (not the range), are derived by using Lyapunov–Krasovski functional method. Those criteria are expressed in the form of linear matrix inequalities and they can easily be checked. Two numerical examples are provided to demonstrate the effectiveness of the obtained results. Copyright © 2012 John Wiley & Sons, Ltd.